1994
DOI: 10.1093/oxfordjournals.aje.a117266
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Patterns and Correlates of Hormone Replacement Therapy Use in Middle-aged Women

Abstract: Patterns of hormone replacement therapy (HRT) use over time and predictors of initiating or discontinuing use were examined in a longitudinal study. A cohort of 2,425 women aged 45-55 years identified from a population-based random survey in Massachusetts in 1981-1982 was followed by six telephone interviews, 9 months apart. Cohort participants were either premenopausal (66.8%) or in early perimenopause (33.2%). During the study, prevalence of use was low overall (12.3%) and was considerably higher for surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
52
3
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(65 citation statements)
references
References 0 publications
8
52
3
2
Order By: Relevance
“…[12][13][14][15][16] HT is currently the gold standard for treatment of vasomotor symptoms. A Cochrane Database systematic review showed a 75% reduction in hot flash frequency with HT compared to placebo.…”
mentioning
confidence: 99%
“…[12][13][14][15][16] HT is currently the gold standard for treatment of vasomotor symptoms. A Cochrane Database systematic review showed a 75% reduction in hot flash frequency with HT compared to placebo.…”
mentioning
confidence: 99%
“…It appeared that women with a longer perimenopausal transition were more likely to report VMS. Very few of the perimenopausal women were treated with ovarian hormone therapy or oral contraceptive agents (45,82).…”
mentioning
confidence: 99%
“…Porém, o estilo de vida saudável, classes sócio-econômicas elevadas, maior escolaridade e o uso de procedimentos preventivos de saúde também influenciam significativamente a utilização de hormônios (Avis & Johanes, 1998). Outros fatores importantes são a presença da sintomatologia climatérica ( Johanes et al, 1994), sendo o uso mais evidente entre mulheres brancas (Dawson & Tompson, 1990;Egland et al, 1988 (1) Teste qui-quadrado de Pearson (*) Falta uma informação TRH = terapia de reposição hormonal blema de caracterizar populações segundo variáveis, como por exemplo, a análise discriminante. Este método tem uma teoria baseada em variáveis contínuas, e, segundo Johnson & Wichern (1982), dentre as alternativas apresentadas pela literatura estatística, uma das mais adequadas seria o uso de modelos de regressão logística.…”
Section: Discussionunclassified